Effect of the compound GIZH -290 and levetiracetam on epileptic activity in rat brain structures on EEG models of bemegrid-induced seizures - T. A. Voronina; S. A. Litvinova; I. G. Kovalev (Фармакокинетика и Фармакодинамика, 2021)
The effect of levetiracetam (a derivative of 4-phenylpyrrolidone) and its original analog, the compound GIZH-290, on primary generalized epileptic activity (EpA) in rat brain structures (sensorimotor cortex, dorsal hippocampus-CA3 field and lateral hypothalamus field) on EEG models of bemegridinduced seizures was studied. It was found that EpA, after the introduction of bemegrid, appears in 1–2 minutes in the form of prolonged generalized high-amplitude discharges and is registered within 3 hours. GIZH-290 (5 mg/kg, intraperitoneal, 15 minutes after bemegrid) causes a significant (p < 0.05) decrease in the number of epileptic discharges in the cortex and at the level of the trend in the hippocampus, which is accompanied by a decrease in the amplitude of the Epi-discharges. Levetiracetam at a dose of 200 mg / kg does not significantly change the severity of paroxysmal activity (the number of convulsive discharges and their duration) caused by bemegrid.